2020
DOI: 10.1111/aor.13738
|View full text |Cite
|
Sign up to set email alerts
|

The Dialyzer Identification Code (DIC): A filter characteristics codification for dialyzer choice in renal replacement therapy

Abstract: The dialyzer is the core element of extracorporeal blood purification therapies where several processes take place depending on specific membrane characteristics. To date, the filter choice requires preliminary knowledge of all its characteristics as they cannot be easily deduced from the commercial trade name, hence the difficulty in identifying easily equivalent dialyzers and clearly comparing single‐filter characteristics. The choice of improper dialyzers for a specific treatment can determine a less‐effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…As sieving coefficient measurements are required by the respective dialyzer standards, also the results from such time‐resolving measurements would be generally comparable between different laboratories. Nalesso et al 23 recently suggested to standardize dialyzer descriptions and to include molecular weight cut‐off and retention onset, which is generally missing in the current dialyzer instruction for use. Our present approach could help to close this gap and may be easier to implement than other measurements, such as dextran measurements, as here special equipment would be necessary, and the standardization would be more complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As sieving coefficient measurements are required by the respective dialyzer standards, also the results from such time‐resolving measurements would be generally comparable between different laboratories. Nalesso et al 23 recently suggested to standardize dialyzer descriptions and to include molecular weight cut‐off and retention onset, which is generally missing in the current dialyzer instruction for use. Our present approach could help to close this gap and may be easier to implement than other measurements, such as dextran measurements, as here special equipment would be necessary, and the standardization would be more complex.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the three dialyzers FX CorAL (Fresenius Medical Care), ELISIO (Nipro), and xevonta (B. Braun) used in the clinical study comPERFORM ( Com parative Clinical Perform ance of Dialyzers Applied During High Volume Online Hemodiafiltration, NCT04102280) 22 . Table 1 summarizes information for dialyzers according to Nalesso et al, 23 for the following categories: Membrane/Area, Coefficients, Clearances, Sieving Coefficients, and Modality. For the categories SC‐MW (molecular weight retention onset and molecular weight cut‐off) and RR (middle and high molecular weight reduction rate) the manufacturers provide no information in the respective instructions for use or brochures.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, errors in the parameters of the EBPT prescription relate to incorrect nomenclature ( 17 , 18 ), blood flow, dialysate flow, total reinfusion flow, unit of measurement of flows, pre- and post-dilution reinfusion percentage, filtration fraction (FF), inappropriate weight loss ( 19 ), anticoagulation settings (citrate, heparin, and low–molecular weight heparin dose) composition of hemodiafiltration bags, and, finally, the discrepancy between prescribed and administered dose that depends on real patient’s weight, dilution factor, and treatment downtime ( Table 1 ). The use of incorrect materials relates to the wrong association between the blood purification technique and the filter characteristics depending on its intended use ( 20 ), and between patient’s acid–base and electrolytic balance and the hemodiafiltration fluid composition ( 14 ). These errors lead to an incorrect formulation of the treatment with possible iatrogenic damage to the patient (for example, electrolytes alterations).…”
Section: The Patient Safety In Ebpt Of Critical Patientsmentioning
confidence: 99%